Some Methods for Development of Analytical Module in Telemedicine System for a Child Monitoring - Levashenko, Vitaly; Karas, Sergey I.; Rusin, Miroslav; Sizov, Evgeny E. (Communications - Scientific letters of the University of Zilina, 2011)
Telemedicine system is system that provides distance medical help and wide application of these systems is started. In the paper two telemedicine systems for pediatrics and specifications of their development are considered. This system will be used for decision different aspects in pediatrics, but both of these systems have similar structure and include special analytical module. The analytical module is used for estimation of initial data and forming of preliminary decision about patient state. Two methods for development of the module are proposed. One of them is based on fuzzy decision trees and second is logistic regression for prediction. These methods are alternative and amplify with one another.